Meninjau Ulang Relasi Agama Kristen dan Agama Leluhur dalam Konteks Gereja Masehi Injili di Timor - Nenohai, Jear Niklas Doming Karniatu (Indonesian Journal of Theology, 2023)
This article examines the relationship between the Christian Evangelical Church of Timor (Gereja Masehi Injili di Timor, or GMIT) and Indigenous religions. It gives special attention to the Monthly Cultural Liturgy (Liturgi Bulan Budaya, or LBB), which is a contextual theological construct instituted by the GMIT Synod. This research explores the limited efficacy of contextual theology as the approach only aids GMIT members in observing aspects of Indigeneity within the context of Christian worship, while the LBB otherwise rejects Indigenous cultural and religious practices as errant and infidel. Despite incorporation of Indigenous values within an ecclesial milieu, the discriminatory attitudes of GMIT members towards Indigenous communities remain unaddressed within the current prism of contextual theology. Consequently, I aim to improve Christian contextual theology through studying other religions by means of the Indigenous religion paradigm. The goal is to create a more inclusive theology that encourages GMIT members to be more open and accepting of local communities practicing Indigenous religions. Such an amalgamation yields an intersubjective paradigm of contextual theology, the upshot of which makes for a more adaptive LBB that fosters relationships within the scope of GMIT’s ministerial services.